Effects of Natalizumab Therapy on Intrathecal Immunoglobulin G Production Indicate Targeting of Plasmablasts. Issue 5 (September 2021) - Schlüter, Miriam; Oswald, Eva; Winklmeier, Stephan; Meinl, Ingrid; Havla, Joachim; Eichhorn, Peter; Meinl, Edgar; Kümpfel, Tania
Abstract : Objectives: To evaluate the long-term effects of natalizumab (NTZ) on different features of intrathecal immunoglobulin (Ig) synthesis in patients with multiple sclerosis (MS) and to quantify the expression of α4-integrin in stages of B-cell maturation. Methods: We combined a cross-sectional (49 NTZ-treated MS patients, mean treatment duration 5.1 years, and 47 untreated MS patients) and a longitudinal study (33 patients with MS before and during NTZ, mean treatment duration: 4.8 years), analyzing paired serum and CSF samples for IgG, IgA, and IgM levels, reactivity against selected viruses (measles virus, rubella virus, and varicella zoster virus [MRZ] reaction), and oligoclonal bands (OCBs). Banding patterns before and after therapy were directly compared by isoelectric focusing in 1 patient. In addition, we determined the expression of α4-integrin by FACS analysis on blood-derived B-cell subsets (plasmablasts, memory B cells, and naive B cells) of healthy controls. Results: In serum, NTZ decreased IgM and IgG, but not IgA, levels. IgM hypogammaglobulinemia occurred in 28% of NTZ-treated patients. In CSF, NTZ treatment resulted in a strong reduction of intrathecally produced IgG and, to a lesser extent, IgA, whereas IgM indices [(Ig CSF/Serum)/(Albumin CSF/Serum)] remained largely unchanged. Reduction of the IgG index correlated with NTZ treatment duration, as did serum IgM and IgA levels. MRZ reaction was unchanged and OCB persisted. Direct comparison of OCB pattern before and after NTZ revealed the persistence of individual bands. α4-Integrin expression was highest on plasmablasts (CD19 + CD38 + CD27 + ). Conclusion: Our data indicate that NTZ reduces short-lived plasmablasts in the CNS compartment but has little effect on locally persisting long-lived plasma cells.